Analisis Pengaruh Firm Size, Sales Growth, Cash Conversion Cycle, Managerial Ownership, Institutional Ownership terhadap Return On Assets pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2019-2024 - Sena Arief Widagda; Foza Hadyu Hasanatina (Diponegoro Journal of Management, 2026)
This study aims to analyze the effects of firm size, cash conversion cycle, sales growth, managerial ownership, and institutional ownerhsip on corporate financial performance as measured by return on assets (ROA). The research is conducted on manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2024. The selected period reflects the dynamics of corporate performance before, during, and after the COVID-19 pandemic, which significantly affected operational activities and corporate profitability. This study employs an explanatory research method with a quantitative approach. The research sample consists of 345 manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2024 period, selected using purposive sampling based on predetermined criteria. The data used are secondary data obtained from companies’ annual financial reports. Data analysis is conducted using panel data regression with the assistance of Stata software. The results indicate that firm size and sales growth have a positive effect on ROA, suggesting that companies with larger asset scales and higher sales growth are more capable of utilizing internal resources efficiently to enhance profitability. The cash conversion cycle has a negative effect on ROA, indicating that efficient working capital management plays an important role in improving corporate financial performance. Meanwhile, managerial ownership and institutional ownerhsip show inconsistent effects on ROA, implying that ownership structure does not always directly contribute to increased corporate profitability. This study is expected to contribute theoretically to the development of financial management literature by strengthening the application of the Resource-Based View in explaining the role of internal firm factors on financial performance. Practically, the findings may serve as a consideration for management, investors, and regulators in formulating strategic policies related to operational efficiency, corporate growth, and ownership structure in manufacturing companies in Indonesia.